MODELING AND SIMULATION FOR INVERTED PENDULUM ON ROTATING DISC - Ab Ghani, Mohd Ruddin; Mohd Amin, Nur Huda; Hyriel Anuar, Kasdirin (2011)
The point of view expressed in this paper will be focused on modeling and simulation for inverted pendulum on rotating disc. The inverted pendulum has been modeled separately into three parts of sub-model as well as DC motor, rotating disc and pendulum models. The stable and unstable system depends on an effect of a torque which is proportional to speed and opposed to motion and force applied to the plant. It shall be argued in this paper that inverted pendulum is one of the unstable systems. The output response will be based on simulation results.